Viral Associations with Chronic Fatigue Syndrome and the Prevalence of Artifacts. - Oakes, Brendan. (2017)
Abstract: Chronic fatigue syndrome (CFS) is a complex, heterogeneous disease affecting more than 1 million Americans. Despite extensive research into the etiology of CFS, no definitive cause of CFS has been determined; however, there is evidence supporting an infectious etiology. In 2009, a study that reported 67% of CFS patients tested positive for the new gammaretrovirus xenotropic murine leukemia virus-related virus (XMRV), as compared to only 3.7% of healthy controls, reignited the quest for a causative viral agent for CFS. Confirming this high prevalence of XMRV in CFS patients would have been a major step forward in defining CFS. Instead, we found that murine DNA contamination in human samples or reagents can result in false-positives when using the sensitive nested PCR to detect XMRV employed by the 2009 study. Failing to detect anti-XMRV antibodies in the sera of patients who previously tested positive for XMRV using the nested PCR confirmed that the samples were, in fact, false-positives. Two viruses under investigation as possible triggers for CFS, Epstein-Barr virus (EBV) and human herpesvirus-6 (HHV-6), can transactivate the human endogenous retrovirus-K18 (HERV- K18) env gene, whose product encodes a superantigen (SAg). SAgs are microbial proteins that greatly over-stimulate the immune system. Thus, these viruses could lead to induction of the HERV-K18 env SAg, which then could lead to overstimulation of the immune system causing the symptoms of CFS. To test this model, we first attempted to associate increased HERV-K18 env transcripts with CFS symptom severity; however, we found HERV-K18 env expression was the same in CFS patients as healthy controls and did not correlate with CFS symptoms. Next, we attempted to link the ubiquitous herpesviruses already suspected as triggers to CFS and inducers of HERV-K18 env, HHV-6 and HHV-7, to HERV-K18 env by measuring viral copy number in CFS patients; however, viral copy number failed to correlate with HERV-K18 env expression. Lastly, because EBV was shown to transactivate HERV-K18 env, we examined the HERV-K18 env genotype in CFS patients with a history of EBV-infectious mononucleosis (EBV-IM) and compared it to CFS patients without a history of EBV-IM. Patients who develop CFS after having EBV-IM could be associated with a susceptible HERV-K18 env genotype that is not present in other CFS patients; however, we failed to find a genotypic difference between these CFS populations in our small cohort. Typical gene association studies employ hundreds, if not thousands, of samples to find significance; thus, future studies should be done on a much larger cohort. Overall, these studies helped focus the HERV-K18 model on a more specific, stratified group of CFS patients with high viral copy numbers of HHV-6 or HHV-7. Also, these studies helped prove, without a doubt, that XMRV is not associated with CFS. Finally, these studies highlight the importance of using multiple methods to confirm results of major new findings.; Thesis (Ph.D.)--Tufts University, 2013.; Submitted to the Dept. of Pharmacology & Experimental Therapeutics.; Advisor: Theoharis Theoharides.; Committee: Martin Beinborn, Michael Court, and Athe Tsibris.; Keywords: Pharmacology, Immunology, and Virology.